A SOCIOLINGUISTIC COMPETENCE OF A TRANSLATOR: SOCIOLINGUISTIC COMPETENCE OF A TRANSLATOR - Norboyeva, Shakhnoza (Журнал иностранных языков и лингвистики, 2022)
In the context of the stringent requirements of the business environment for the effectiveness of communications, the translator should particularly clearly determine the social context, take into account the gender aspect of the language forms used by the participants of communication (males and females).